Unusual organism causing pyocystis in an immunosuppressed haemodialysis patient. (30th March 2016) - Elsayed, Mohammad; Finn, Arkadiy; Dapaah-Afriyie, Kwame
Abstract : A 68-year-old man with end-stage renal disease and a history of orthotopic cardiac transplantation on chronic immune suppression therapy presented to the emergency department with fever and purulent urethral discharge. He was diagnosed with pyocystis (bladder abscess). Culture of the urethral discharge showed Trueperella bernardiae . The patient improved after 3 days of bladder irrigation with normal saline and gentamicin. This case demonstrates that bladder abscess is a potential source of infection in an oliguric patient. This is the first report to describe the opportunistic pathogen, T. bernardiae, as the causative agent in pyocystis.